Identifikasi Sawah Irigasi Teknis Tidak Produktif di Kota Metro Berbasis Sistem Informasi Geografis dan Citra Landsat 8 OLI - Ridwan, Ridwan; Amin, Muhammad; Asmara, Sandi; Asshidiq, Miftahul Huda (Jurnal Agricultural Biosystem Engineering, 2024)
Much of Metro City still serves asa technical irrigation site. The Metro City rice commodity is a strategic commodity that needs serious attention to its management and development, since farmers and their productivity are predominately high. The research aimed at knowing the condition of the irrigation doors in UPTD Pengairan Metro irrigation areas, knowing the extent of the tracts of fields of potential and function according to irrigation areas, and knowing the condition of the technical irrigation fields by means of a method of interpretation of the image of landsat 8 OLI. The study uses NDVI (Normalized Difference Vegetation Index) vegetative index method and NDBI (Normalized Difference Built-up Index). NDBI is used to identify the growing sequence of MT1 2020-2022. NDVI is used to score a layer of vegetative fragility in Metro City. The condition of the irrigation doors in UPTD Pengairan Metro of 57 irrigation gates in existence, 53 are in good condition and the remaining 4 are damaged. Comparative of the large tracts of rice field in the Sekampung Bunut area of potential amounting to 2,070 ha and an area of function of 1,466 ha. For Sekampung Batanghari, area of potential area of 1,696 ha and an area of function of 1,457 ha. The technical irrigation state of the rice fields in Metro City was studied vegetation is rare with NDVI a value of 0.15. From the NDVI MT1 classification in 2020-2022 years, it is identified that the damage to irrigation doors in the fields of technical irrigation became unproductive marked by the change of color in the northern region of the city from 2020 to 2022. Keywords : NDBI, NDVI, The Image Of Landsat 8, Technical Irrigation Rice.